2010
DOI: 10.1007/s12552-010-9023-1
|View full text |Cite
|
Sign up to set email alerts
|

A Clearer Picture of Multiracial Substance Use: Rates and Correlates of Alcohol and Tobacco Use in Multiracial Adolescents and Adults

Abstract: Existing studies indicate that multiracial adolescents face greater substance use rates than monoracial adolescents. However, it is unclear whether the risk identified in adolescence persists into adulthood. The current study uses data from the of drinking and smoking behavior for mixed-race individuals-comparing them to other racial groups. We review the limitations of our design and the implications for future research on multiracial substance use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…For example, White+African American students reported higher past 12-month alcohol use and 5+ drinking than African American students, and White+Hispanic students reported higher past 12-month use than Hispanic students. Adolescents who identify as multiracial tend to report higher risk for alcohol and other substance use (Chavez & Sanchez, 2010; Choi et al, 2006; Goings et al, 2016; Price et al, 2002). Among adolescents, multiracial identity (not limited to any particular race combinations) is associated with higher stress, which is associated with higher health and behaviors risks, including alcohol use (Udry, Li, & Hendrickson-Smith, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, White+African American students reported higher past 12-month alcohol use and 5+ drinking than African American students, and White+Hispanic students reported higher past 12-month use than Hispanic students. Adolescents who identify as multiracial tend to report higher risk for alcohol and other substance use (Chavez & Sanchez, 2010; Choi et al, 2006; Goings et al, 2016; Price et al, 2002). Among adolescents, multiracial identity (not limited to any particular race combinations) is associated with higher stress, which is associated with higher health and behaviors risks, including alcohol use (Udry, Li, & Hendrickson-Smith, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Some research has found that increased likelihood of substance use among adolescents reporting more than one racial/ethnic identity is part of a group of problem behaviors, including violence and racial discrimination (Choi et al, 2006). As the percentage of the population that identifies with more than one racial/ethnic group continues to expand, improved understanding of the extent of differences in alcohol risk (and risk for other substance use) across multiracial groups is needed (Chavez & Sanchez, 2010; Price et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Native American youth populations show higher rates of alcohol and marijuana use than youth of other minority groups, and are found to have rates equal or higher than those of White youth (Clark, Doyle et al, 2013; Johnson et al, 2015; Wallace et al, 2003; Wu et al, 2015). Higher rates of alcohol and marijuana use have also been reported among Multiracial youth then their monoracial minority peers (Clark, Doyle et al, 2013; Johnson et al, 2015; Wu et al, 2015), although mixed findings have been noted in comparison to White peers depending on the biracial subgroups one identifies with (e.g., White-Native American; White-Black; White-Asian; Black-Hispanic; Chavez & Sanchez, 2010; Clark, Doyle et al, 2013; Clark, Nguyen, & Kropko, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…However, despite discrimination rate differences, the highest rates of alcohol use among adolescents and young adults have been observed for White, Multiracial (those who belong to more than one racial group), Native American, and Latino individuals (e.g., Chavez & Sanchez, 2010; Chen, Balan, & Price, 2012; Goings, Butler-Bente, McGovern, & Howard, 2016; O’Malley & Johnston, 2002; Terry-McElrath & Patrick, 2018). Additionally, other work demonstrates that 4-year college attendance is positively associated with heavy alcohol use for White students but inversely related for both Black and Asian students (Paschall, Bersamin, & Flewelling, 2005).…”
mentioning
confidence: 99%